Optimum release angle in the shot put - Linthorne, N. P. (Journal of Sports Sciences, 2001)
The aim of the study was to assess the accuracy of a method of calculating the optimum release angle in the shot put. Using the proposed method, the optimum release angle that produces the greatest flight distance is calculated by combining the equation for the range of a projectile in free flight with the relations between release speed, release height and release angle for the athlete. The method was evaluated using measurements of five college shot-putters who performed maximum-effort throws over a wide range of release angles. When the athletes threw with high release angles, the shot was released from a greater height above the ground and with a lower release speed. For all five athletes, the calculated optimum release angle was in good agreement with the athlete's preferred release angle. Each athlete had his own specific optimum release angle because of individual differences in the rate of decrease in release speed with increasing release angle. Simple models of shot-putting were developed to explain the relations between release speed, height and angle in terms of the anthropometric and strength characteristics of the athlete.